10.8k views
2 votes
I need help with 6,7,8,9

I need help with 6,7,8,9-example-1
User Janjonas
by
5.9k points

1 Answer

3 votes
Hi there!


6. x² + 6x = 27
subtract 27 on both sides to make the equation equal to 0.
x² + 6x - 27 = 0
(x - 3)(x + 9) = 0
x - 3 = 0 x + 9 = 0
x = 3 x = -9

7. k² - 13k + 36 = 0
(k - 9)(k - 4) = 0
k - 9 = 0 k - 4 = 0
k = 9 k = 4


8. g(x) is translated up 5 from f(x).

9. g(x) is reflected by x-axis, then translated 3 down from f(x).



Hope this helped! :)
User Baba Yaga
by
5.7k points